Work-Life Balance and Professional Development: Their Impact on Employee Performance - Badaruddin, Badaruddin; Surianto, Surianto; Fatmasari, Fatmasari (Fakultas Ekonomi, Universitas Muslim Indonesia, 2024)
This study explores the relationships between work-life balance, professional development, and employee performance, focusing on how these factors interact to enhance job satisfaction, productivity, and skill development. The research employed a qualitative approach, utilizing in-depth interviews, focus groups, and observational data to gather insights from employees across various organizations. The study analyzed how work-life balance and professional development initiatives impact employee performance and organizational culture. The findings indicate that a balanced work environment, coupled with access to professional development opportunities, significantly enhances employee performance. Employees with a healthy work-life balance reported lower stress levels and higher job satisfaction, leading to increased productivity. Additionally, professional development was found to improve technical and managerial skills, boosting confidence and job competence. The synergy between work-life balance and professional development created a supportive environment that promoted both personal well-being and professional growth, resulting in a positive feedback loop of engagement and performance. This study highlights the importance of integrating work-life balance policies with continuous professional development programs to achieve sustainable employee performance and organizational success. It underscores the critical role of transformational leadership and supportive organizational culture in fostering a productive work environment. Future research should explore these relationships quantitatively and across diverse industries to further validate and expand upon these findings.